SEJARAH PENGKAFIRAN DAN MARGINALISASI PAHAM KEAGAMAAN DI MELAYU DAN JAWA (Sebuah Telaah Sumber) - Fathurrahman, Oman (Universitas Islam Negeri Raden Intan Lampung, 2011)
The history of Islamization in the archipelago, especially that happened since the 16th century has encouraged a writing tradition of religious manuscripts in huge numbers. The manuscripts can definitely be regarded as primary sources for reconstruction a social- intellectual history of Indonesian Islam in the past. One of the most important topics discussed in such sources is that relates to the history of blaming and marginalization of religious doctrine, especially that of Unity of Being (wahdat al-wujūd), or popularly known in Java as Manunggaling Kawula Gusti. This article will examine some Islamic works covering the discourse of controversy between the orthodoxy and heterodoxy that emerged since the mid of 16th and 19th centuries in the Archipelago. The first work that will be consulted is a Sufi treatise entitled at-Tuhfah al-Mursalah ila an-Nabi (the Gift addressed to the spirit of the Prophet) written by an Indian scholar, Fadl Alla>>>h al- Hindi al-Burhanpuri. Furthermore, this article will demonstrate the emergence of ‘derivative’ local works of at-Tuhfah, written both in Arabic and local languages. The works contain both opposing and supporting thoughts of the theosophical doctrine discussed in the at- Tuhfah.